2012
DOI: 10.1161/circinterventions.111.967901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parallel Micro-Engineered Stent Grooves on Endothelial Cell Migration, Proliferation, and Function

Abstract: D rug-eluting stents (DES) have dramatically reduced the long-term rate of reintervention and improved clinical outcomes among patients undergoing percutaneous coronary interventions.1 However, DES use still carries a small but critically important cumulative risk of late stent thrombosis. Human pathology studies suggest that delayed healing leads to incomplete strut coverage, which has been associated with late thrombotic events.2 Moreover, early DES platforms elicited enhanced platelet adhesion 3 and endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…51 Parallel microgrooves increases endothelial cell migration rates. 52,53 Corneal epithelium cells were directed to migrate along the parallel grooves 54 (groove and ridge width of 1, 2, 5, and 10 μ m, groove depth of 1 and 5 μ m). These effects are different from the effect of nanoparticles on cellular migration, which strengthened intracellular tension and retard cellular migration.…”
Section: Discussionmentioning
confidence: 99%
“…51 Parallel microgrooves increases endothelial cell migration rates. 52,53 Corneal epithelium cells were directed to migrate along the parallel grooves 54 (groove and ridge width of 1, 2, 5, and 10 μ m, groove depth of 1 and 5 μ m). These effects are different from the effect of nanoparticles on cellular migration, which strengthened intracellular tension and retard cellular migration.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, microgroove development based on laser technology allowed to establish the ideal boundary conditions for endothelial cell (EC) migration speed and groove configuration, therefore aiding optimisation of engineering parameters 9. Recent technology developments using photolithographic techniques have achieved a markedly improved resolution in the development of the microgroove patterns 3. Accuracy of the manufacturing process has improved over time and allowed the development of groove features in the micron range.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have described delayed healing and neoatherosclerosis as the most important biological mechanisms responsible for this condition 2. In the experimental setting, accelerated strut endothelialisation results in the more rapid development of a lower and more organised neointimal response even in the absence of antiproliferative drugs 3. Then, technologies capable of accelerating strut endothelialisation have the potential to improve the safety profile of DES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that already at 3 days post-implantation, the coronary artery stent endothelialization was significantly increased in the microgrooved stents (81.3%) compared with the smooth surface stents (67.5%). Moreover, at 28 days, the neointimal thickness was significantly lower in the microgrooved stent group compared with the smooth surface controls [103] . These results indicate that an enhanced rate of early endothelialization and significant inhibition of the neointimal hyperplasia can be achieved by the application of an appropriate surface structure to the bare metal stents.…”
Section: Nanoscale Structure Modificationsmentioning
confidence: 82%